Investigating the Effectiveness of Solution Focused Couples Therapy (SFCT) on the Inefficiency of the Function of Couples Referring to Counseling Centers in Shiraz - Amir Keshavarzi; Mehdi Zare Bahramabadi; Shohreh Ghorban Shiroudi; Seyed Ali Hosseini Al-Madani (International Journal of Psychosocial Rehabilitation, 2026)
Background and Propose: healthy function of family prevents problems such as addiction, divorce, infidelity, boredom, diversity and much harm. The study aim was investigating the effectiveness of solution-focused couple’s therapy (SFCT) on the inefficiency of the function of couples referring to counseling centers in Shiraz. Method: This quasi-experimental study was performed using a pretest-posttest design with a control group. The statistical population of the study was maladapted couples referring to counseling centers in Shiraz in 2018. Sixty people (30 pairs) were randomly selected as experimental groups (15 pairs) and 15 pairs as a control group. The data collection tool was the McMaster Family Assessment Device Scale. In this study, multivariate covariance test (MANCOVA) was used. Results: The results of multivariate analysis of covariance (MANCOVA) on the mean scores of inefficiency of family function in pre- and post-test of experimental and control groups showed a significant difference in the inefficiency of family function variable (p <0.0001). One-way analysis of covariance in MANCOVA text was also based on the mean scores of post-test of inefficiency of family function of experimental and control groups with pre-test control (p <0.0001 and F=172.59), which indicates the degree of effect or difference, and shows the percentage of individual differences in post-test scores of variables related to the effect of solution focused couple’s therapy (SFCT). Conclusion: the results of the analysis showed the originality and importance of the solution-focused couple’s therapy (SFCT) intervention in reducing the inefficiency of the function of incompatible couples and the mentioned variable can explain the high degree of variability in the function of couples in incompatible conditions.